HUBUNGAN ANTARA PRESTASI BELAJAR PADA MATA PELAJARAN FIQIH DENGAN PENGAMALAN IBADAH SHALAT SISWA KELAS III MI AL-FUDHOLA KABUPATEN BEKASI - Nadyah Mahmudah M; Oking Setia Priatna; Ahmad Sobari (Jurnal Akrab Juara, 2019)
This research is the phenomenon specifically as happened to the students of MI Al-Fudhola Bekasi Regency which is often found by students who ignore the five daily prayers. The formulation of the problem in this study is there a relationship between Learning Achievement in Fiqh Subjects with the implementation of Prayer at Third Class of MI Al-Fudhola Bekasi District?. The method used in this study is a survey method with correlational analysis techniques, which is a study that aims to find the relationship or influence of two or more variables. The sample in the study were grade III students of MI Al-Fudhola Bekasi Regency, amounting to 27 students. Based on the results of the study show there is a correlation between Learning Achievement in Fiqh Subjects with implementation of Prayer at third class of MI Al-Fudhola Bekasi. It is shown that rxy = 0.591> rt (0.05) = 0, 444 and rxy = 0.591> rt (0.01) = 0.561. Thus there is a positive relationship between Learning Achievement in Jurisprudence Subjects with Implementation in Prayer for Third Class Students of Al-Fudhola MI Bekasi District is accepted or proven to be true.